Reframing citizenship education: The shifting portrayal of citizenship in curriculum policy in the province of Ontario, 1999-2018 - Jesse K. Butler; Peter Milley (Arizona State University, 2020)
State-mandated curriculum policy documents have an important political function. Governments use them to make ideological statements about the role of schools and how the next generation of citizens are to be shaped. Beginning from this premise, we use a frame analysis methodology to examine how citizenship in the Province of Ontario, Canada is framed in four consecutive versions of the curriculum policy documents that prescribe citizenship education for secondary schools. Our analysis spans 20 years, during which two political parties - one conservative, the other liberal - held power. Our inductive analysis is presented using a typology of citizenship with five dimensions: political, public, cultural, juridical, and economic. We illustrate consistency across the decades, including a preoccupation with: 1) external and internal threats to the stability and unity of Canada (political); 2) fostering nationalistic identification (political); 3) developing transferrable skills for the globalized economy (economic); 4) establishing a pre-set role for the individual citizen, characterized by legal and ethical obligations (juridical). We reveal a gradual de-emphasis of opportunities for citizens to actively participate in reshaping their communities and society (public, cultural). This shift in the political and ideological meaning of citizenship conceives citizens as isolated individuals in a reified state and society.